Prevalence of bronchial asthma and its associated factors among children of known population: an epidemiological study - Sukhani, Vijay Kumar; Banu, Nasima (International Journal of Contemporary Pediatrics, 2018)
Background: Asthma is widely known as a multifactorial respiratory disorder with both genetic and environmental underlying risk factors. Exposures to common allergens and air pollution from various sources have all been implicated as triggers of the disease. Chronic respiratory diseases are leading cause of death worldwide. The objective of this study was to study the prevalence of bronchial asthma and its associated factors among children of known population. Methods: Community-based cross-sectional study consisting of 400 children. Data was obtained from two government schools and two private schools. Both males and females aged below 10 years were selected for the study. A pretested and validated questionnaire was designed. Results: The prevalence of asthma in current asthmatics in present study was found to be 20%. The prevalence rate was higher among those with family history of asthma. 82.5% current asthmatics were suffering from rhinitis. Conclusions: Asthma is a common problem faced in today world especially in children the symptoms and risk factors should not be ignored. Those with family history of asthma should take precautions.